Qualidade de vida e vulnerabilidade social na percepção do idoso - Soares, Pamela de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
According to data from the World Health Organization, the older population will grow sixteenfold from 1950 to 2025 in comparison to a fivefold population growth in the same period, which is referred to by UNO as the “Ageing Era”. This places Brazil in the sixth position in the contingent of older individuals worldwide, with a number that is higher than 32 million. Considering how topics such as quality of life and social vulnerability are important in face of the growing older population, these topics must be furthered studied so that they can be understood as important variables for both better clinical practice and scientific research. To describe the social vulnerability and evaluate the quality of life of older individuals in a population hospitalized in the internal medicine ward of Bauru State Hospital. This is a descriptive qualitative study that was conducted by means of interviews and using Bardin’s discourse analysis. The inclusion criteria used in this study were: individuals at 60 years of age who were mentally capable of answering the proposed questions. Two categories concerning Quality of Life and Social Vulnerability emerged from the interviews. The following emerged from the theme Quality of Life: “Life as something important” and subcategories that involved feeling useful in society, having a supportive family, independence, optimism and joy and survival. Also, the following emerged from the theme Social Vulnerability: “Negative recognition of older individuals in society” and subcategories that involved lack of respect, functional disability, family indifference, housing-related insecurity, an inefficient health care system and loneliness. Quality of Life and Social Vulnerability are largely discussed themes in the present scenario. In this study, it was possible to perceive that the older population needs social support, effective public... (Complete abstract click electronic access below)

Entre 1950 e 2025, segundo dados da Organização Mundial de Saúde, a população presente na chamada terceira idade crescerá cerca de 16 vezes, contra 5 vezes o crescimento populacional, esse período chamado pela ONU como a “Era do Envelhecimento”, colocando o Brasil na sexta posição em contingente de idosos no mundo, significando um número superior a 32 milhões. Levando-se em consideração como são importantes as temáticas de qualidade de vida e vulnerabilidade social, tendo em vista a crescente população idosa, se faz necessário aprofundar tais temas, entendendo-os como variáveis importantes tanto para uma melhor prática clínica, como pra pesquisa científica. Descrever a vulnerabilidade social e avaliar a qualidade de vida dos idosos de uma população internada na enfermaria de clínica médica do Hospital Estadual Bauru. Trata-se de um estudo descritivo, com abordagem qualitativa, realizado através de entrevistas com análise do discurso de Bardin. Este trabalho usou como critério de inclusão pessoas com 60 anos com capacidade mental para responder as perguntas propostas. Surgiram a partir das entrevistas duas categorias, no que se referiam Qualidade de Vida e Vulnerabilidade Social. Da temática Qualidade de Vida surgiu “A vida como algo importante” e subcategorias que envolviam sentir-se útil na sociedade, ter família como suporte, autonomia, otimismo e alegria e sobrevivência. Da temática Vulnerabilidade Social surgiu “Reconhecimento negativo da pessoa velha pela sociedade” e subcategorias que envolviam falta de respeito, incapacidade funcional, indiferença familiar, porto-inseguro no que se refere à moradia, sistema de saúde ineficiente e solidão. Qualidade de vida e Vulnerabilidade social são duas temáticas muito discutidas no contexto atual. Nesta pesquisa foi possível perceber que a população envelhecida necessita de subsídios, de suporte... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Idosos - Aspectos sociais; Assistencia a velhice; Qualidade de vida